The Spectrum of SPTA1-Associated Hereditary Spherocytosis - Chonat, Satheesh; Risinger, Mary; Sakthivel, Haripriya; Niss, Omar; Rothman, Jennifer A.; Hsieh, Loan; Chou, Stella T.; Kwiatkowski, Janet L.; Khandros, Eugene; Gorman, Matthew F.; Wells, Donald T.; Maghathe, Tamara; et al. (Frontiers in Physiology, 2019)
Hereditary spherocytosis (HS) is the most common red blood cell membrane (RBC) disorder causing hereditary hemolytic anemia. Patients with HS have defects in the genes coding ankyrin (ANK1), band 3 (SLC4A1), protein 4.2 (EPB42), and  (SPTA1) or -spectrin (SPTB). Severe recessive HS is most commonly due to biallelic SPTA1 mutations. -spectrin is produced in excess in the normal erythroid cells, therefore SPTA1-associated HS ensues with mutations causing significant decrease of normal protein expression from both alleles. In this study, we systematically compared genetic, rheological, and protein expression data to the varying clinical presentation in eleven patients with SPTA1-associated HS. The phenotype of HS in this group of patients ranged from moderately severe to severe transfusion-dependent anemia and up to hydrops fetalis which is typically fatal if transfusions are not initiated before term delivery. The disease severity correlated to reduced SPTA1 mRNA expression in the patients’ reticulocytes and the levels of -spectrin protein in their RBC cytoskeleton but was also affected by other factors. Patients carrying the low expression αLEPRA allele in trans to a null SPTA1 mutation were not all transfusion dependent; their anemia improved or resolved with partial or total splenectomy respectively. Patients with near-complete or complete -spectrin deficiency had suboptimal reticulocytosis or reticulocytopenia, were transfusion dependent and their anemia did not significantly improve with splenectomy; they require either lifetime transfusions and chelation or stem cell transplant. Comprehensive genetic and phenotypic evaluation is critical to provide accurate diagnosis in patients with SPTA1-associated HS and guide towards appropriate management.